(untitled) (Journal of Medical & Health Sciences Review, 2025)
The changes in healthcare coupled with advanced technologies have impacted the nursing profession in ways that are both beneficial and disadvantageous to new nurses. Technologies such as EHRs, artificial intelligence clinical decision support systems, Telehealthcare, and other advanced technologies have enhanced healthcare delivery systems, but they have also expanded the magnanimity of the nursing practice. New nurses should be trained on the new clinical workload and the challenges of handling work with technology hence the need for supervision to enable the nurses to change and grow professionally. This paper focuses on caregivers, specifically new nurses’ supervisors and mentors, and how they can help new nurses to on board digitally enabled environments. Interviews were used, and participants were selected from mentors and supervisors who have been in the profession for a considerable amount of time to determine the main difficulties faced, the strategies used, and the ideal practices. In evaluating the results it was observed that structured mentorship, technology integrated skills training and organizational backing play a significant role in developing new generation nurses’ digital literacy and assurance. Also, the effectiveness of the mentors in managing identified issues such as digital fatigue, how learning can be phased, and the overall wellbeing of nursing professionals cannot be undermined. The challenges described in the study make it clear that it is necessary to continue developing consensus with regard to digital training offered within the framework of nursing education and to raise the issue of incorporating the principles of mentorship into the healthcare legislation. Mentoring specific adaptation issues can significantly enhance nursing staff retention, satisfaction, and care delivery in the context of digital transformations in healthcare organizations. This paper brings insight into the literature surrounding digital transformation in the area of healthcare and offers practical suggestions for enhancing the suitability of the current mentoring models to prepare new nurses for the roles and responsibilities associated with the growing application of technology in clinical practice.